Retrospective study of radiographic changes in athletic bulls with orthopedic disorders - Cholfe, Bruno F.; Silva, José R.B. [UNESP]; Filho, Alfredo M.; Souza, Caroline G.; Filho, Antônio M.T.; Perri, Silvia H.V. [UNESP]; Vulcano, Luiz C. [UNESP]; Rodrigues, Celso A. [UNESP] (FapUNIFESP (SciELO), 2019)
The objectives of this study were to demonstrate the lesions that affect athlete bulls and to correlate the disorders with weight, age, affected limb and region of the limb. The present study was accomplished using radiographic images of athletic rodeo bulls collected from the medical and surgical records of the large animal service at the veterinary hospital. Radiographic images were evaluated for 136 bulls that were taken care of at the Veterinary Hospital, ranging in age from 4 to 13 years, with an average weight of 800kg and proven prior physical activity through participation in rodeos. The chi-square or Fisher’s exact test was used to assess the association between the studied variables. It was observed that 71.6% of the bulls studied and suffering from lameness had radiographic lesions, predominantly in experienced animals. Enthesopathy in starter and experienced bulls, septic arthritis in starter bulls, and fractures and degenerative joint disease in experienced bulls were the most frequent radiographic lesions diagnosed. The region of limb where the majority of radiographic changes occurred was the digits. Risk factors and occurrence of diseases of the locomotor system in athletic bulls are similar to those in sport equines.
Estudo retrospectivo das alterações radiográficas de touros atletas com doenças ortopédicas